If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(-1x + -5) = -80 Reorder the terms: 10(-5 + -1x) = -80 (-5 * 10 + -1x * 10) = -80 (-50 + -10x) = -80 Solving -50 + -10x = -80 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '50' to each side of the equation. -50 + 50 + -10x = -80 + 50 Combine like terms: -50 + 50 = 0 0 + -10x = -80 + 50 -10x = -80 + 50 Combine like terms: -80 + 50 = -30 -10x = -30 Divide each side by '-10'. x = 3 Simplifying x = 3
| 5(3x-1)+4(2x+7)= | | 7+6=11 | | x^2+2xy+2y^2-2y+1=0 | | 2(a+5)=25 | | 3x+2y-2z=-1 | | 4(3z-2)-2(z+1)=3(z+2)-1 | | n-47=(-49) | | (-7/10)2 | | (X-4)=3(2x+1) | | 6x+1-6x=5 | | 2(4x+5)-5x=4-3(x-5) | | 2x+3y-3x=1 | | (X-4)+5=3(2x+1) | | A+66=94 | | 5x+6x-68=34-6x | | xsquared-Kx+3-K=0 | | 5(p-10)=80 | | 9x+3y=-24 | | 3+6y=9+3y | | 0=0.25x^4-x^3+x^2 | | x-y+4z=4 | | 25=11+0.6x | | v^3-2v-16v=-32 | | 5+6y=6+3y | | (x*cos(y)-y*sen(y))dy+(x*sen(y)+y*cos(y))dx=0 | | ((8x^8y^2)/(x^-2y^-3))^-1 | | 5t+360t= | | 0.1*x^2+x+2.5=0 | | 11m-30=18m-9 | | 16+(2)=(2)-4x | | 5t-11=23 | | 5*e^2x-1=4 |